Read like a man: comparing narratives of masculinity in adolescent literature - Hernandez, Francisco; Macaluso, Michael (Frontiers in Sociology, 2024)
Recent movements like #MeToo and #TimesUp have surfaced and challenged ideas about masculinity in popular conversations. In particular, these ideas have centered around “toxic masculinity”—a version of masculinity that reflects stereotyped, dated, and even dangerous expectations for manhood. This notion of masculinity can be reinforced in a number of ways, especially through pop culture, where it runs the risk of becoming commonly accepted or normalized. This study evaluates the narratives of masculinity in three different novels that are marketed toward high school-aged students in the United States: Lord of the Flies; Gabi, A Girl in Pieces; and Aristotle and Dante Discover the Secrets of the Universe. Using a critical literacy lens, this study considers the symbols, behaviors, expectations, and meanings given to masculinity in and through each novel and considers the implications of this analysis for adolescent readership inside and outside of schooling. The study concludes that the more contemporary novels showcase a range of masculine portrayals, including positive, affirming versions of masculinity, compared to a more singular and pessimistic one found in a novel traditionally used in schools. Thus, the study concludes that formal schooling may be an important way to address and disrupt unhealthy versions of masculinity.